Volcanic Lakes - Rouwet, Dmitri; Christenson, Bruce; Tassi, Franco; Vandemeulebrouck, Jean.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book aims to give an overview on the present state of volcanic lake research, covering topics such as volcano monitoring, the chemistry, dynamics and degassing of acidic crater lakes, mass-energy-chemical-isotopic balance approaches, limnology and degassing of Nyos-type lakes, the impact on the human and natural environment, the eruption products and impact of crater lake breaching eruptions, numerical modeling of gas clouds and lake eruptions, thermo-hydro-mechanical and deformation modeling, CO2 fluxes from lakes, volcanic lakes observed from space, biological activity, continuous monitoring techniques, and some aspects more. We hope to offer an updated manual on volcanic lake research, providing classic research methods, and point towards a more high-tech approach of future volcanic lake research and continuous monitoring.
Introduction -- Volcano-hydrologic Hazards from Volcanic Lakes -- The Chemical Composition and Evolution of Volcanic Lakes -- Gases in Volcanic Lake Environments -- Isotope Fractionation and HCl Partitioning During Evaporative Degassing from Active Crater Lakes -- Molten Sulfur Lakes of Intraoceanic arc Volcanoes -- Crater Lake Energy and Mass Balance -- CO2 Degassing from Volcanic Lakes -- The Comparative Limnology of Lakes Nyos and Monoun, Cameroon -- Modelling Air Dispersion of CO2 from Limnic Eruptions -- Microbial Life in Volcanic Lakes.
Keywords: Geochemistry; Geoecology; Environmental geology; Microbiology; Geophysics; Geochemistry; Geoecology/Natural Processes; Applied Microbiology; Geophysics and Environmental Physics